FAKTOR YANG MENYEBABKAN DIKABULKANNYA GUGATAN CLASS ACTION TERHADAP PERBUATAN MELAWAN HUKUM OLEH PEMERINTAH KOTA PAYAKUMBUH DALAM KERUGIAN TEMPAT PEMBUANGAN AKHIR (TPA) - Ade Wahyuni; Benny Rusli; Syuryani Syuryani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
It is true that for every aspect of negligence committed by a legal subject which then harms other legal subjects and impacts the environment, it is clear that there must be concrete action to obtain this justice. The strategy used by this community uses a class action lawsuit strategy and can produce very satisfying results. The nature of the research used is descriptive, namely research that aims to provide data that is as precise as possible about the circumstances that are the object of research. Then the problem approach used is a sociological juridical approach, namely by searching for data by interviewing informants. Sources of data and legal materials used are secondary data, namely data obtained through interviews with several related parties and also includes books, supporting literature on the subject matter discussed and statutory regulations. The results of this study are the legal consequences in the lawsuit of compensation from the defendant to the plaintiff and the winning factor is the class action strategy to win the dispute.